Higher Education and Police An International View (Springer International Publishing, 2018)
This edited collection is concerned with the ideas, challenges, demands and framework of conditions behind police education from an international perspective. Whilst not directly concerned with a classical comparison of education concepts from different countries, the broad range of international contributors consider issues such as professionalization programmes, how higher education programmes influence police organizations, as well how higher education influences police practice in a global context. Examining a wide array of countries from Germany to China and Brazil to show the flawed nature of an education system based purely upon an approach concerned with police officer numbers, the editors of this book argue for the need for greater scientific education among police around the world to meet contemporary developments. A timely and well-informed study, this book meets a crucial gap in the literature and will serve as an important contribution to existing work on policing, crime prevention, and theoretical criminology.